Kemampuan Pemecahan Masalah Mahasiswa Dalam Menyelesaikan Soal Cerita Bilangan Bulat - Yumi Sarassanti (Tadris Matematika, 2024)
The purpose of the research is to describe students' abilities in solving integer problems in the form of story problems based on predetermined indicators. This research took the form of a qualitative descriptive study involving 33 students. Data collection uses test techniques in the form of essay questions. Based on the results of the analysis of problem-solving abilities in solving integer problems, it was found that many students already understood presenting problems in word problems. Although there are some students who are still not careful in solving questions, especially when doing calculations and drawing conclusions. Students are also able to formulate mathematical problems correctly using the knowledge they must solve whole numbers. Some students can carry out calculations correctly to solve the problems presented so that it can be said that students have achieved indicators of problem-solving ability in whole numbers.